There is a better way: Eight recommendations on the science system in New Zealand - Campbell, Hamish; Lillis, David; Grieve, Janet (New Zealand Science Review, 2005)
​Although there is much that is positive about the New Zealand research science and technology system, an increasing sense of dysfunction is emerging within the research community. Ad hoc patching of the system (including the development of new funding schemes to address funding gaps)has characterised science portfolio management since 2000.Further, the effectiveness of the policy/funder/provider separation principle is now in question and the efficacy of information sharing and joint policy development of these parties in doubt. The sense of dysfunction is compounded by inadequate public funding of research, science and technology(RS&T). If New Zealand is to become a ‘Knowledge Society’, public funding of RS&T must increase by at least 25%to match the OECD benchmark average percentage of GDP.Attention must be paid to ‘system coherence’, the role of individual institutions, and the usefulness of using whole-of-government outcomes to manage the RS&T system. The conflicting incentives that the current RS&T funding arrangements give to universities and crown research institutes(CRIs) must be corrected so that optimum educational outcomes and research results are achieved in the long-term interests of New Zealand.